Island in the sky [videorecording (DVD)] - Wayne, John, 1907-1979; Gann, Ernest K. (Ernest Kellogg), 1910-1991; Nolan, Lloyd; Abel, Walter, 1898-1987; Arness, James, 1923-2011; Devine, Andy, 1905-1977; Gann, Ernest K. (Ernest Kellogg), 1910-1991 (John Wayne collection., 2005)
A transport plane crashes on Labrador's frozen tundra. The pilot must keep his crew alive while waiting to be rescued. Based on the novel by Ernest K. Gann.